(3GdHjFI h GdJfejI GdSjGMjI (B/s - (3GdGSOj, SdGe LYaQs; (3GdHWGW, Ydjs; (3Rjf GdOjf, cGXe CMeOs ((3YeGf(B: s (3OGQ GdGjGe(B, s, 2014)
(3jVe GdHjFI hGdJdhK hGdedhKGJ GdHjFjI, CSGSjGJ GdSjGMI, GdSjGMI GdOjfjI aj cQHdGA GdebOSI, GdJfejI GdSjGMjI , GdJfejI GdSjGMjI GdeSJOGeI, GdJMOjGJ GdJi JhGLg GdJfejI GdSjGMjI(B.s
(3GdeQGLY U(B.191s
Keywords: (3GdHjFIs; (3GdJfejI GdHjFjIs; (3GdJfejI GdeSJOGeIs; (3JfejI GdSjGMIs